Interosseous artery as an access artery in case of late radial artery occlusion. Issue 7 (4th May 2017) - Babunashvili, Avtandil M.; Pancholy, Samir B.
Abstract : We report a new technique of arterial access through the ipsilateral interosseous artery in a case of late radial artery occlusion (RAO). RAO, although not frequent, is a limiting iatrogenic complication after transradial intervention (TRI) and precludes repeat use of the same radial artery for future procedures. Our technique involves obtaining access to the ipsilateral radial artery (RA) in the distal postocclusion segment and use of collateral channel between this segment and the interosseous artery (IOA) for advancing a guidewire and sheath in the IOA lumen and in brachial artery thereafter. © 2017 Wiley Periodicals, Inc.